If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = 3(a + 2b) + -3b 0 = (a * 3 + 2b * 3) + -3b 0 = (3a + 6b) + -3b Combine like terms: 6b + -3b = 3b 0 = 3a + 3b Solving 0 = 3a + 3b Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3a' to each side of the equation. 0 + -3a = 3a + -3a + 3b Remove the zero: -3a = 3a + -3a + 3b Combine like terms: 3a + -3a = 0 -3a = 0 + 3b -3a = 3b Divide each side by '-3'. a = -1b Simplifying a = -1b
| 2+cosx=0 | | 2+2cosx=0 | | x^2=18y^2-y^4 | | 8ab+12ab-12a= | | 7(h+1)=3+7h | | 3(g-1)=-2(2+g) | | 36x^2y^3+xy^2= | | =b(b+3)-2 | | =6(a+3)+2 | | =8a+2(5-b)-2a | | 6x^3+4x^2-14x+4=0 | | 125r^2-45= | | 3(2d+3)=12 | | 12r^2-75= | | =13a-b+3-6a+b | | 18.50+d=26.5 | | =7+a(3+b)-2 | | (49x^2-14x+1)(49x^2-15x+1)=0 | | =3+6(8+b)+2(b+b) | | =3a-4+2b-a+11 | | 15x^2+2xy-8y^2= | | 8.5+1m= | | =4a*3a | | =4*a-2(3*a-5) | | =4a-2(3a-5) | | 25b^2-195b-40= | | log(3)m=2-log(3)n | | 8x+7=9x+2 | | 2c-10=-28 | | -5x-7x= | | =b*(b+3)-2 | | =6a-7+9a+4 |